Culture Analysis Of Cultural Feeding With Early Breast Milk Complementary Food In The Clinic Arrahmah District Bangil Pasuruan District - Rifatul Lailiyah; Retno Palupi Yonni Siwi (Journal for Research in Public Health, 2023)
There are still many mothers who provide additional breastfeeding (MP-ASI) to babies less than four months old. Giving complementary foods too early has a very high risk of contamination risk, namely the incidence of gastroenteritis which is very dangerous for the baby and can reduce milk production because the baby rarely breastfeeds. The purpose of this study was to analyze the cultural relationship factor by offering early complementary foods. The method used in this research is correlational analytic with cross sectional approach. The population was all mothers breastfeeding infants aged 0–6 months at the Arrahman clinic in Pasuruan. The sampling technique used purposive sampling. The independent variable of the cultural factor and the dependent variable is the offering of early solids. The research instrument used a questionnaire. Analysis of research results using the chi square test. The results showed that most of 25 people (78.1%) had no cultural factors, 24 people (75%) did not provide complementary feeding. The results of the cross tabulation showed that 22 people (68.75%) had no cultural factors and did not provide early complementary foods to their children, the Chi Square test results showed 0.001, which means that there is a relationship between cultural factors and early complementary feeding. This shows that mothers who follow cultural factors have a tendency to provide complementary feeding to infants aged 0-6 months and mothers who do not follow cultural factors do not provide complementary foods to babies aged 0-6 months. The solution that is needed is to provide information through counseling by health workers about the provision of early complementary foods which will have a negative impact on the baby, namely the baby's digestive system is not disturbed so that nutritional disorders and will reduce the baby's immune system because the baby is not exclusively breastfed until the age of 6 months.